Integrating An Instructional Design Model In Video Development For Autism Spectrum Disorder - Che Ku Mohd, Che Ku Nuraini; Shahbodin, Faaizah; Meylinda Maria, Meylinda Maria; Sedek, Muliati; Mohamad, Siti Nurul Mahfuzah (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
The interest in using video among individuals with autism spectrum disorder (ASD) has increased significantly. By using video is able to engage them actively in social activities. Due to that, a deep attention in understanding the potential of video development has been a top priority. Integrating an instructional design video for learning process can help the students to pay more attention and understanding while learning in the classroom. The purpose of the study is to know the details of every part of the learning system process. It is important for features to improve the autism’s skill for better understanding while learning process happened. It would be more effective if ADDIE or Dick and Carey’s model as the framework develop this instructional design. Based on the results, the respondents are satisfied with the usage of video. The use of ICT needs to be enhanced to students with autism. The usage of the video under teacher super-vision and use of mind challenging videos.